A case study of international circular migrants shack-farming in the Bon Accord Agricultural Holdings, Tshwane, South Africa. - Ngwenya, Jockia Lucky (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2014.